A tungsten-doped oxide solid electrolyte and preparation method thereof

By doping Li1.5Al0.5Ge1.5(PO4)3 with +5-valent tungsten element, Li1.5-xAl0.5Ge1.5-xWx(PO4)3 oxide solid electrolyte is formed, which solves the problem of ion conductivity of oxide electrolyte It solves the problem of low conductivity and achieves high conductivity and simple process, which has commercial potential.

CN118299651BActive Publication Date: 2025-01-21HUANGGANG NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410459217.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-17
Publication Date
2025-01-21
Estimated Expiration
2044-04-17

AI Technical Summary

Technical Problem

The existing oxide solid electrolyte has low ionic conductivity and is difficult to meet the safety and performance needs of lithium-ion batteries.

Method used

By doping Li1.5Al0.5Ge1.5(PO4)3 with +5-valent tungsten element, an oxide solid electrolyte of Li1.5-xAl0.5Ge1.5-xWx(PO4)3 is formed to improve its lithium ion conductivity. Rate.

Benefits of technology

The doped electrolyte has extremely high lithium ion conductivity, close to 1*10-3S/cm, which meets the basic ion conduction requirements of solid-state batteries. At the same time, the synthesis process is simple and fast, and has commercial value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118299651B_ABST
    Figure CN118299651B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion battery materials, and discloses a tungsten-doped oxide solid electrolyte and a preparation method thereof. The structural formula of the oxide solid electrolyte is Li 1.5‑ x Al 0.5 Ge 1.5‑x W x (PO4)3 can be used as a solid electrolyte in lithium-ion batteries. The present invention uses tungsten carbide as a tungsten source and successfully dopes +5 tungsten ions into Li by high-temperature calcination in an air environment. 1.5 Al 0.5 Ge 1.5 In (PO4)3 compounds, the modified Li 1.5‑x Al 0.5 Ge 1.5‑x W x The color of (PO4)3 changes from pure white to blue-purple, but it still maintains a pure phase, and the ionic conductivity is greatly improved. 1.5‑x Al 0.5 Ge 1.5‑x W x (PO4)3 oxide solid electrolyte has high ionic conductivity and simple preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a tungsten-doped oxide solid electrolyte and a preparation method thereof. Background Art

[0002] In recent years, domestic new energy vehicles have developed rapidly, and the key to new energy vehicles lies in power battery technology. At present, the batteries used in new energy vehicles are lithium-ion batteries. Lithium-ion batteries are flammable because the liquid electrolyte in the battery (i.e., a mixed solution of ester compounds and sodium salts) contains ester organic compounds, which are very easy to burn or even explode under high temperature or collision conditions. Therefore, it is urgent to solve the problem of power battery safety.

[0003] Using solid electrolytes to replace liquid electrolytes to prepare all-solid-state batteries is an important way to improve safety performance. The reason is that the solid electrolytes in all-solid-state batteries will not decompose and burn when exposed to high temperatures. At present, research on lithium-ion solid electrolytes at home and abroad mainly focuses on two types of electrolytes: oxides and sulfides. Among them, sulfide electrolytes such as Li 6 PS 5 Cl and Li 10 G 2 S 12 It has extremely high ionic conductivity (1*10 -2 S / cm), which is comparable to traditional electrolytes. However, the extremely high cost of sulfides and their instability to air make it difficult for sulfide solid electrolytes to be commercialized and widely used. Oxide electrolytes such as Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 With Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Stable to air and inexpensive, it has the potential for commercialization, but the ionic conductivity of oxide solid electrolytes is low, usually only 1*10 -4 S / cm or so.

[0004] Cation doping is an effective method to improve the ionic conductivity of solid electrolytes. 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 Doping with Sc, Mg, B and other elements in the Al position, or doping with Ge 4+ Position Ti 4+At the same time, most of the literature reports point out that the use of cation doping with different valence states to create defects in Li positions is a good way to improve Li + Effective means of ionic conductivity, for example, the review (Defect Strategy in Solid-State Lithium Batteries. Small Methods 2024, 8(1), e2301162) lists Li 7 La 3 Zr 2 O 12 Oxide electrolytes use +2-valent Ba to dope +3-valent La positions to create Li vacancy defects to improve conductivity. 1.5 A l 0.5 Ge 1.5 (PO 4 ) 3 The Ge in the nucleus has a valence of +4, and can be doped with elements with a valence of +5 and a similar ionic radius to achieve the purpose of creating lithium vacancy defects.

[0005] Therefore, modifying oxide solid electrolytes and improving the ionic conductivity of oxide electrolytes are of great significance to the development of solid-state lithium-ion batteries. Summary of the invention

[0006] In view of this, the present invention proposes a tungsten-doped oxide solid electrolyte and a preparation method thereof, aiming to improve the problem of low conductivity of oxide solid electrolytes in low-cost lithium-ion batteries.

[0007] On the one hand, the present invention proposes a tungsten-doped oxide solid electrolyte, the structural formula of which is Li 1.5- x Al 0.5 Ge 1.5-x W x (PO 4 ) 3 , where the valence of the W element is +5, 0≤x≤1.5.

[0008] On the other hand, the present invention provides a method for preparing a tungsten-doped oxide solid electrolyte, comprising the following steps:

[0009] S1: mixing a lithium source, an aluminum source, a germanium source, a tungsten source and a phosphorus source, wherein the tungsten source is tungsten carbide;

[0010] S2: solid phase ball milling;

[0011] S3: calcining the solid phase ball milled material;

[0012] S4: Repeat S2-S3, the number of repetitions is 0-1 times, to obtain the chemical solid electrolyte.

[0013] Preferably, the rotation speed of the solid phase ball mill is 365-425 rpm, and the ball milling time is 8-12 h.

[0014] Preferably, the calcination temperature is 400-970° C., and the calcination time is 5-10 h.

[0015] Preferably, before the calcination, the material is formed by cold pressing to obtain the material in sheet form.

[0016] Further preferably, the cold pressing pressure is 10-15 MPa.

[0017] Preferably, the solid phase ball milling and the calcination are both performed under air atmosphere.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] After doping, Li 1.5 A l 0.5 Ge 1.5-x W x (PO 4 ) 3 The electrolyte has extremely high lithium ion conductivity, close to 1*10 -3 S / cm, which meets the basic ion conduction requirements of solid-state batteries; at the same time, the synthesis method of the present invention is simple and fast, making Li 1.5 Al 0.5 Ge 1.5-x W x (PO 4 ) 3 Solid-state electrolytes have great commercial value both in terms of electrochemical performance and synthesis process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0021] Figure 1 This is a comparison of the appearance of the three tungsten sources, tungsten carbide, tungsten sulfide and tungsten trioxide, before and after high-temperature calcination in air environment;

[0022] Figure 2 For WC, 2 O 5 and Nb 2 O5 Comparison of the products after calcination of LAGP doped with three different +5-valent metal sources;

[0023] Figure 3 XRD comparison diagram of LAGP doped with different amounts of +5-valent tungsten;

[0024] Figure 4 This is a comparison of the macro powders of LAGP doped with different amounts of tungsten;

[0025] Figure 5 It is a comparison diagram of the AC impedance between Comparative Example 1 and Example 2. DETAILED DESCRIPTION

[0026] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] Example 1

[0028] A tungsten-doped oxide solid electrolyte Li 1.5-x Al 0.5 Ge 1.5-x W x (PO 4 ) 3 The preparation method of (x=0.125) is prepared by the following preparation steps:

[0029] 1) Add 0.1375 mol lithium hydroxide, 0.025 mol aluminum oxide, 0.1375 mol germanium oxide, 0.3 mol ammonium dihydrogen phosphate and 0.0125 mol tungsten carbide into a ball mill, set the ball mill speed to 385 rpm, and the ball milling time to 10 h;

[0030] 2) After collecting the above mixed materials, cold pressing is performed at 12 MPa to obtain precursor small discs;

[0031] 3) Place the precursor wafer in step 2) in a muffle furnace, set the temperature to 450° C., and calcine for 8 hours. Finally, collect the reaction product.

[0032] 4) Pour the product in step 3) back into the ball mill, set the ball mill speed to 385 rpm, and the ball milling time to 10 h. After ball milling, cold press the powder at 12 MPa to obtain a disc.

[0033] 5) The disc in step 4) is placed in a muffle furnace, the temperature is set to 950° C., and the calcination time is 8 hours. Finally, the product after the reaction is crushed into powder for subsequent characterization.

[0034] Example 2

[0035] A tungsten-doped oxide solid electrolyte Li 1.5-x Al 0.5 Ge 1.5-x W x (PO 4 ) 3 The preparation method of (x=0.25) is prepared by the following preparation steps:

[0036] 1) Add 0.125 mol lithium hydroxide, 0.025 mol aluminum oxide, 0.125 mol germanium oxide, 0.3 mol ammonium dihydrogen phosphate and 0.025 mol tungsten carbide into a ball mill, set the ball mill speed to 400 rpm, and the ball milling time to 8 h;

[0037] 2) After collecting the above mixed materials, cold pressing is performed at 11 MPa to obtain precursor small discs;

[0038] 3) Place the precursor wafer in step 2) in a muffle furnace, set the temperature to 400° C., and calcine for 10 hours. Finally, collect the reaction product.

[0039] 4) Pour the product in step 3) back into the ball mill, set the ball mill speed to 400 rpm, and the ball milling time to 10 h. After ball milling, cold press the powder at 11 MPa to obtain a disc.

[0040] 5) The disc in step 4) was placed in a muffle furnace, the temperature was set to 960° C., and the calcination time was 9 h. Finally, the product after the reaction was crushed into powder for subsequent characterization.

[0041] Example 3

[0042] A tungsten-doped oxide solid electrolyte Li 1.5-x Al 0.5 Ge 1.5-x W x (PO 4 ) 3 The preparation method of (x=0.375) is prepared by the following preparation steps:

[0043] 1) Add 0.1125 mol lithium hydroxide, 0.025 mol aluminum oxide, 0.1125 mol germanium oxide, 0.3 mol ammonium dihydrogen phosphate and 0.0375 mol tungsten carbide into a ball mill, set the ball mill speed to 365 rpm, and the ball milling time to 11 h;

[0044] 2) After collecting the above mixed materials, cold pressing is performed at 10 MPa to obtain precursor small discs;

[0045] 3) Place the precursor wafer in step 2) in a muffle furnace, set the temperature to 440° C., and calcine for 5 hours. Finally, collect the reaction product.

[0046] 4) The product in step 3) was poured back into the ball mill, the ball mill speed was set to 365 rpm, the ball milling time was set to 11 h, and after the ball milling, the powder was cold pressed at 10 MPa to obtain a disc.

[0047] 5) The disc in step 4) is placed in a muffle furnace, the temperature is set to 970° C., and the calcination time is 10 h. Finally, the product after the reaction is crushed into powder for subsequent characterization.

[0048] Example 4

[0049] An oxide solid electrolyte Li 1.5-x Al 0.5 Ge 1.5-x W x (PO 4 ) 3 The preparation method of (x=0.5) is prepared by the following preparation steps:

[0050] 1) Add 0.1 mol lithium hydroxide, 0.025 mol aluminum oxide, 0.1 mol germanium oxide, 0.3 mol ammonium dihydrogen phosphate and 0.05 mol tungsten carbide into a ball mill, set the ball mill speed to 425 rpm, and the ball milling time to 12 h;

[0051] 2) After collecting the above mixed materials, cold pressing is performed at 15 MPa to obtain precursor small discs;

[0052] 3) Place the precursor wafer in step 2) in a muffle furnace, set the temperature to 480°C, and calcine for 8 hours. Finally, collect the reaction product.

[0053] 4) The product in step 3) was poured back into the ball mill, the ball mill speed was set to 425 rpm, the ball milling time was set to 12 h, and after the ball milling, the powder was cold pressed at 15 MPa to obtain a disc.

[0054] 5) The disc in step 4) is placed in a muffle furnace, the temperature is set to 950° C., and the calcination time is 8 hours. Finally, the product after the reaction is crushed into powder for subsequent characterization.

[0055] Comparative Example 1

[0056] The difference between this comparative example and Example 2 is that x=0, that is, no tungsten source doping is added, and the other steps are the same.

[0057] Specifically, 0.15 mol lithium hydroxide, 0.025 mol aluminum oxide, 0.15 mol germanium oxide, and 0.3 mol ammonium dihydrogen phosphate were added into a ball mill.

[0058] Comparative Example 2

[0059] The difference between this comparative example and Example 2 is that Ta 2 O 5 Replace tungsten carbide for doping, and the rest of the steps are the same.

[0060] Comparative Example 3

[0061] The difference between this comparative example and Example 2 is that Nb 2 O 5 Replace tungsten carbide for doping and the rest of the steps are the same.

[0062] The oxide solid electrolyte products of all the above examples and comparative examples were subjected to XRD analysis using a D8 XRD analyzer produced by Bruker, Germany.

[0063] The specific operation process is: load the target test sample into the sample stage, 0.01° / step, and the test range is 10°-50°.

[0064] The sodium ion solid electrolyte products of all the above embodiments and comparative examples were subjected to conductivity tests, and AC impedance tests were performed using a French Bio-Logic electrochemical workstation.

[0065] First, 400 mg of oxide solid electrolyte sample was weighed and placed in a mold with a diameter of 10 mm. The oxide solid electrolyte was pressed into a small disc using a pressure of 10 MPa. After gold powder slurry was applied to both ends of the disc, it was placed in the test mold for AC impedance testing. The AC impedance Hertz setting range is 100 MHz-10 μHz. After the impedance data is tested, the ionic conductivity of the sample is calculated.

[0066] Evaluation results

[0067] Figure 1This is a comparison of the products of three tungsten sources, tungsten carbide, sulfide and tungsten trioxide, after high-temperature calcination in air. According to the data, blue tungsten has a valence of +5, brown tungsten has a valence of +4, and green tungsten has a valence of +6. Figure 1 As shown in the figure, in the present invention, under the calcination condition in air, tungsten carbide eventually becomes +5-valent blue tungsten, tungsten sulfide becomes +4-valent brown tungsten, and tungsten trioxide does not change and remains +6-valent. Since tungsten carbide is cheaper than +5-valent blue tungsten and tungsten carbide can directly generate +5-valent blue tungsten at a high temperature of 900°C, tungsten carbide can be used as a cheap tungsten source for W treatment of LAGP. 5+ Ion doping.

[0068] Figure 2 To use WC, 2 O 5 and Nb 2 O 5 Comparison of the products of LAGP doped with three different +5-valent metal sources after calcination. It can be seen that the use of tungsten carbide doping will make LAGP turn purple, and the XRD phase after doping remains pure; while the use of Ta 2 O 5 or Nb 2 O 5 The products doped with LAGP all produced impurities, which indicated that the use of Ta 2 O 5 and Nb 2 O 5 LAGP cannot be effectively doped.

[0069] Figure 3 This is a comparison diagram of XRD of LAGP doped with different amounts of tungsten. It can be seen that in Example 4 (i.e., when the tungsten carbide doping amount reaches x=0.5), a small amount of impurity peaks (# symbol position) appear in the XRD, and when the doping amount x≤0.375, the XRD of Comparative Example 1, Example 1, Example 2, and Example 3 can all maintain a pure phase.

[0070] Figure 4 This is a comparison of the macro powders of LAGP doped with different amounts of tungsten. It can be seen that as the tungsten doping amount increases, the color of the electrolyte product will gradually deepen from light purple to dark purple.

[0071] Figure 5 2 is a comparison diagram of the AC impedance of comparative example 1 and example 2. It can be seen that the semicircle of example 2 after using tungsten carbide as the tungsten source doping is smaller, indicating that the mass transfer impedance of example 2 is smaller than the mass transfer impedance of comparative example 1, and the ion conductivity of example 2 is higher. Therefore, using tungsten carbide to dope LAGP with tungsten can effectively improve the ion conductivity of the LAGP electrolyte.

[0072] Table 1 shows the conductivity results of the oxide solid electrolyte products of all embodiments and all comparative examples. It can be seen from Table 1 that the ion conductivity of the comparative examples is significantly lower than that of the embodiments of the present application, which illustrates the technical contribution of the doping method of the present application using tungsten carbide as a tungsten source to the improvement of LAGP ion conductivity. The reason may be that the +5-valent W ions replace the +4-valent Ge ions, resulting in Li + Vacancy defects, thereby increasing Li + The rate at which ions migrate in a crystal lattice.

[0073] Table 1 Conductivity of oxide solid electrolytes

[0074] Sample name Ionic conductivity (S / m) Comparative Example 1 <![CDATA[Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 ]]> <![CDATA[1.73*10 -4 ]]> Comparative Example 2 <![CDATA[Li 1.25 Al 0.5 Ge 1.25 Ta 0.25 (PO 4 ) 3 ]]> <![CDATA[8.91*10 -6 ]]> Comparative Example 3 <![CDATA[Li 1.25 Al 0.5 Ge 1.25 Nb 0.25 (PO 4 ) 3 ]]> <![CDATA[3.46*10 -5 ]]> Example 1 <![CDATA[Li 1.375 Al 0.5 Ge 1.375 IN 0.125 (AFTER 4 ) 3 ]]> <![CDATA[6.05*10 -4 ]]> Example 2 <![CDATA[Li 1.25 Al 0.5 Ge 1.25 IN 0.25 (AFTER 4 ) 3 ]]> <![CDATA[9.03*10 -4 ]]> Example 3 <![CDATA[Li 1.125 Al 0.5 Ge 1.125 IN 0.375 (AFTER 4 ) 3 ]]> <![CDATA[5.82*10 -4 ]]> Example 4 <![CDATA[LiAl 0.5 GeW 0.5 (PO 4 ) 3 ]]> <![CDATA[2.38*10 -4 ]]>

[0075] In summary, the +5 cation-doped Li 1.5 A l 0.5 Ge1 .5-x Mx(PO 4 ) 3 (M=W, Ta, Nb) oxide solid electrolyte and its preparation method, first studied For Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 Zhongge 4+ The effect of site doping is only observed when W is used. 5+ After doping, the product has no impurity phase, while using Ta 5+ or Nb 5+ The samples after doping all showed impurities, indicating that only W 5+ Suitable for Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 Then the present invention studied different W 5+ Effect of doping amount on Li 1.5 Al 0.5 Ge 1.5-x W x (PO 4 ) 3 The influence of ionic conductivity. 1.5 Al 0.5 Ge 1.5-x W x (PO 4 ) 3 The electrolyte has extremely high lithium ion conductivity, close to 1*10 - 3S / cm, which meets the basic ion conduction requirements of solid-state batteries; at the same time, the synthesis method of the present invention is simple and fast, making Li 1.5 Al 0.5 Ge 1.5-x W x (PO 4 ) 3 Oxide solid electrolytes have great commercial value both in terms of electrochemical performance and synthesis process.

[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A tungsten-doped oxide solid electrolyte, characterized in that: The oxide solid electrolyte has a structural formula of Li 1.5-x Al 0.5 Ge 1.5-x W x (PO4)3, wherein the valence of the W element is +5, and 0.125≤x≤0.

5.

2. A method for preparing a tungsten-doped oxide solid electrolyte, characterized in that: For preparing the oxide solid electrolyte according to claim 1, the preparation method comprises the following steps: S1: mixing a lithium source, an aluminum source, a germanium source, a tungsten source and a phosphorus source, wherein the tungsten source is tungsten carbide; S2: solid phase ball milling; S3: calcining the solid phase ball milled material; S4: Repeat S2-S3, the number of repetitions is 0-1 times, to obtain the chemical solid electrolyte.

3. The method for preparing a tungsten-doped oxide solid electrolyte according to claim 2, characterized in that: The rotation speed of the solid phase ball mill is 365-425 rpm, and the ball milling time is 8-12 h.

4. The method for preparing a tungsten-doped oxide solid electrolyte according to claim 2, characterized in that: The calcination temperature is 400-970° C., and the calcination time is 5-10 h.

5. The method for preparing a tungsten-doped oxide solid electrolyte according to claim 2, characterized in that: Before the calcination, the material is formed by cold pressing to obtain the sheet-shaped material.

6. The method for preparing a tungsten-doped oxide solid electrolyte according to claim 5, characterized in that: The pressure of the cold pressing molding is 10-15 MPa.

7. The method for preparing a tungsten-doped oxide solid electrolyte according to claim 2, characterized in that: The solid phase ball milling and the calcination are both performed under air atmosphere.